2015
DOI: 10.1111/iej.12544
|View full text |Cite
|
Sign up to set email alerts
|

Guided endodontics: accuracy of a novel method for guided access cavity preparation and root canal location

Abstract: 'Guided Endodontics' allowed an accurate access cavity preparation up to the apical third of the root utilizing printed templates for guidance. All root canals were accessible after preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
190
1
38

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(237 citation statements)
references
References 31 publications
8
190
1
38
Order By: Relevance
“…(), Zehnder et al . () and Connert et al . () assessed stent guided access preparations by superimposing a post‐access CBCT upon a pre‐operative designed access.…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 86%
See 1 more Smart Citation
“…(), Zehnder et al . () and Connert et al . () assessed stent guided access preparations by superimposing a post‐access CBCT upon a pre‐operative designed access.…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 86%
“…Zehnder et al . () and Connert et al . () also found small deviations from the intended access (0.12–0.34 mm at the tip of the bur) and a mean angular deviation of less than 2°.…”
Section: Review Of Endodontic Applicationsmentioning
confidence: 86%
“…Another innovative approach to treat teeth with pulp canal calcifications and periapical pathosis is the fusion of an intra‐oral scan with CBCT data to produce a template for a guided access cavity preparation and root canal localisation. Although this technique seems to be promising, it was not tested in molars up to now, but there is already a proof‐of‐principle ex vivo study and a single case report.…”
Section: Discussionmentioning
confidence: 99%
“…They found a 0.99 mm horizontal deviation (ranging from 0.0 to 6.5 mm) at the level of the implant platform of the osseointegrated implants, a 1.24 mm horizontal deflection (ranging from 0.0 to 6.9 mm) at the osseointegrated implant apex and an average angle deviation of 3.81° (ranging from 0.0° to 24.0°) to the longitudinal osseointegrated implant axis . Buchgreitz et al evaluated ex vivo the accuracy of a preparation procedure planned for teeth with root canal obliteration using a guide rail concept based on CBCT scan merged with an optical surface scan and the mean distance between the drill path and the target was significantly lower than 0.7 mm and Zehnder et al concluded that deviations of planned and prepared access cavities were low with means ranging from 0.16 to 0.21 mm for different aspects at the base of the bur and 0.17–0.47 mm at the tip of the bur and the mean of angle deviation was 1.81° . In the field of endodontics, the use of guided splints assisted by CBCT has been documented for treating dens invaginatus and teeth with root canal calcification and apical pathology; this lack of precision can make it difficult to locate the root canals and may lead to unexpected complications.…”
Section: Discussionmentioning
confidence: 99%